2019
DOI: 10.1117/1.jbo.24.12.126001
|View full text |Cite
|
Sign up to set email alerts
|

Corneal thickness measurement by secondary speckle tracking and image processing using machine-learning algorithms

Abstract: Corneal thickness (CoT) is an important tool in the evaluation process for several disorders and in the assessment of intraocular pressure. We present a method enabling high-precision measurement of CoT based on secondary speckle tracking and processing of the information by machine-learning (ML) algorithms. The proposed configuration includes capturing by fast camera the laser beam speckle patterns backscattered from the corneal-scleral border, followed by ML processing of the image. The technique was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…CNN and combined SVM-linear and CNN models alone are able to achieve up to 100% accuracy [ 79 ]. Corneal thickness can also be measured using an automated process via CNN, which involves a secondary speckle tracking (tracking of a laser beam speckle pattern backscattered from corneal-scleral border) and processing of the obtained data by a CNN [ 80 ]. This method was reliable and accurate with a 26 μm of mean fit error, which is comparable to existing pachymetry tools [ 80 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…CNN and combined SVM-linear and CNN models alone are able to achieve up to 100% accuracy [ 79 ]. Corneal thickness can also be measured using an automated process via CNN, which involves a secondary speckle tracking (tracking of a laser beam speckle pattern backscattered from corneal-scleral border) and processing of the obtained data by a CNN [ 80 ]. This method was reliable and accurate with a 26 μm of mean fit error, which is comparable to existing pachymetry tools [ 80 ].…”
Section: Main Textmentioning
confidence: 99%
“…Corneal thickness can also be measured using an automated process via CNN, which involves a secondary speckle tracking (tracking of a laser beam speckle pattern backscattered from corneal-scleral border) and processing of the obtained data by a CNN [80]. This method was reliable and accurate with a 26 μm of mean fit error, which is comparable to existing pachymetry tools [80]. Diabetic peripheral neuropathy is one of the most prevalent complications of diabetes mellitus, and is found in more than 50% of diabetic patients [81].…”
Section: Endothelial Cell Countmentioning
confidence: 99%
“…The results showed that the determination of orbital stops is very accurate and the implementation is faster. 7 Shen incorporated the principle of image processing through a specially designed experimental setup. He meshed the image with a fine ink pen and recorded every moment with a digital camera.…”
Section: Related Workmentioning
confidence: 99%
“…A suggested configuration involves rapidly capturing pictures of incoming stops from smart track stops and then processing the images. The results showed that the determination of orbital stops is very accurate and the implementation is faster 7 . Shen incorporated the principle of image processing through a specially designed experimental setup.…”
Section: Related Workmentioning
confidence: 99%